Analysis of Foot-Ankle Coordination, Agility, and Self-Confidence Towards The Ball-Drifting Skills Of Extra-Curricular Students of SMP Negeri 1 Binamu (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This type of research is path analysis, The subjects of this study were extracurricular students of SMP Negeri 1 Binamu, totalling 30 male students. Data analysis using SPSS 30.00 using descriptive tests, normality tests and hypothesis tests. It is known that there is a direct effect of Foot-Eye Coordination (X1) on Self-Confidence (X3) in extracurricular football students of SMP Negeri 1 Binamu, based on the results of the analysis obtained in the table shows that the coefficient value ß is -0.313 with a calculated -0.800 and significance (p) = 0.067 (p -0.718)